Isolation and characterization of a cDNA encoding Drosophila transcription factor TFIIB. - Yamashita, S (1992)
A Drosophila cDNA encoding a human transcription factor TFIIB homologue was isolated by PCR methods. The deduced amino acid sequence indicates 85% sequence similarity with human TFIIB, and the corresponding cDNA product expressed in Escherichia coli is interchangeable with human TFIIB for both basal and GAL4-VP16-induced transcription. Structural motifs including the direct repeats, basic repeats, and sigma sequence similarities are well conserved among Drosophila, human, and Xenopus TFIIB. However, the N-terminal region of each direct repeat is less conserved among the three species, suggesting the presence of two structural subdomains in the direct repeat. Moreover, the amino acid changes in the N-terminal subdomain produce altered positions of the conserved amino acids between the direct repeats. An overall similarity in general structural features between TFIIB and TFIID tau (the TATA-binding subunit of TFIID) was previously noted. However, in contrast to the sequence divergence reported for the N-terminal domains of TFIID tau from different species, the N-terminal sequence of TFIIB was highly conserved among the species. This suggests that TFIIB has a more rigid structure, consistent with its function as a "bridging" protein between TFIID and RNA polymerase II. Further implications of the TFIIB structure are discussed.